GAMBARAN PELATIHAN KETERAMPILAN OTOMOTIF DI BALAI LATIHAN KERJA INDUSTRI (BLKI), KOTA PADANG - Bobby Satria (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2015)
This research was background be the success of the trainers after follow the automotive skill education and training to get the job. The aims this research to describe automotive skill learning that related for (1) learning material, (2) learning method, (3) learning sources, (4) learning of means and infrastructure, and (5) learning evaluation of Balai Latihan Kerja Industri (BLKI) Padang. This research in form of quantitative descriptive. The population are about 32 peoples. This research sample is automotive skill training participants of BLKI Padang counted 20 peoples. Sampling in this study conducted by cluster random sampling technique. Technique data collecting is enquette. Technique analyse research data is descriptive analysis. From the result of the research found that: (1) automotive skill learning material categorized excellent, (2) the use of learning methods automotive skills categorized excellent, (3) implementation of automotive skills learning in terms of learning resources, categorized as very good, (4) learning of means and infrastructure categorized excellent, (5) learning evaluation have be very good category. The fifth both of the research are very influence for the BLKI Padang participants to get a job in the other profession.